Civic Continuities in an Age of Revolutionary Change, c.1750-1850 Europe and the Americas - Pollmann, Judith; te Velde, Henk (Palgrave Studies in Political History, 2023)
This open access book explores the role of continuity in political processes and practices during the Age of Revolutions. It argues that the changes that took place in the years around 1800 were enabled by different types of continuities across Europe and in the Americas. With historians of modernity tending to emphasise the rise of the new, scholarship has leaned towards an assumption that existing modes of action, thought and practice simply became extinct, irrelevant or at least subordinate to new modes. In contrast, this collection examines continuities between early modern and modern political cultures and organization in Europe and the Americas. Shifting the focus from political modernization, the authors examine the continued relevance of older, often local, practices in (post)revolutionary politics. By doing so, they aim to highlight the role of local political traditions and practices in forging and enabling political change. The book argues that while political change was in fact at the centre of both the old and new polities that emerged in the Age of Revolutions, it coexisted with, and was indeed enabled by, continuities at other levels.